Disease Recurrence in Sentinel Node-Positive Breast Cancer Patients Forgoing Axillary Lymph Node Dissection - Cyr, Amy (2012)
BACKGROUND: Clinically node-negative breast cancer patients usually undergo sentinel lymph node (SLN) biopsy. When metastasis is identified, completion axillary lymph node dissection (CALND) is recommended. Newer data suggest that CALND may be omitted in some women as it does not improve local control or survival. METHODS: Women with a positive SLN diagnosed between 1999 and 2010 were included in this review and were stratified according to whether they did or did not undergo CALND. Primary endpoints included recurrence and breast cancer-specific mortality. Differences between the groups and in time to recurrence were compared and summarized. RESULTS: Overall, 276 women were included: 206 (79 %) women who underwent CALND (group 1) and 70 (21 %) women in whom CALND was omitted (group 2). Group 1 patients were younger, had more SLN disease, and received more chemotherapy (P <0.05 for each). The groups did not vary by tumor characteristics (P >0.05 for each). Median follow-up was 69 (range 6–147) and 73 (range 15–134) months for groups 1 and 2, respectively. Five (2 %) women in group 1 and three (4 %) women in group 2 died of breast cancer (P = 0.39). Local–regional or distant recurrence occurred in 20 (10 %) group 1 patients and in 10 (14 %) group 2 patients (P = 0.39). On multivariate analysis, only estrogen receptor negativity and lymphovascular invasion predicted for recurrence. CONCLUSIONS: Omission of CALND in women with SLN disease does not significantly impact in-breast, nodal, or distant recurrence or mortality. Longer-term follow-up is needed to verify that this remains true with time.